Dynamic electro-thermal modeling of solar cells and modules. (February 2019) - Guerriero, Pierluigi; Codecasa, Lorenzo; d'Alessandro, Vincenzo; Daliento, Santolo
Highlights: The model gives the electro-thermal behavior of PV panels, under varying irradiance. A temperature-dependent macrocircuit based on one-diode model describes each cell. A feedback network determines the temperature of individual cells. COMSOL identifies the feedback network thanks to an effective extraction method. The temperature in each node of the COMSOL mesh can be achieved. Abstract: An accurate model describing the electro-thermal behavior of solar modules, subject to varying irradiance conditions, is presented. The model relies on an enhanced version of the popular one-diode model, implementing the temperature dependence of the parameters by means of a thermal feedback network. The feedback network is built by exploiting a very effective analytical approach which reduces computational efforts and allows an automated solution. The cell-level discretization allows the description of the temperature distribution over solar cell surfaces in panels subject to mismatch events (e.g., partial shading, localized soiling, etc.), along with its time evolution. Experiments performed on a partially shaded solar string evidence good agreement with the model. In uniform condition the temperature error is less than 3 °C, while, under mismatch, the error on the maximum temperature of a cell subject to hot spot is limited to 5 °C.